Landasan Ontologis dalam Pengembangan Kurikulum Pendidikan Agama Islam pada Mata Pelajaran Fikih Madrasah Aliyah - Rohmatulloh, Rifqi (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
The curriculum is a tool used to achieve educational goals and also as a guide in the learning process. There are many approaches to curriculum development, but so the development of Islamic religious education has mostly used academic and humanistic subject approaches. This research aims to examine how academic and humanistic subject approaches are used in developing the Islamic religious education curriculum. This research is based on a literature study with data originating from library sources, including research journals, books, and other documents relevant to the research focus. The results of this research reveal that the development of the Islamic religious education curriculum uses an academic approach by the substance of Islamic religious education itself which contains religious teachings that are systematically arranged to be passed on to students, from an ontological perspective concerns the nature of the curriculum. The epistemology review presents methods of curriculum implementation, while the axiology review explores why the Islamic Religious Education curriculum is implemented and what the aims of the curriculum are.